Tracking the role of Fe in NiFe-layered double hydroxide for solar water oxidation and prototype demonstration towards PV assisted solar water-splitting. (6th January 2021) - Antony, Rajini P.; Betty, C.A.; Tyagi, Deepak; Banerjee, Atindra Mohan; Pai, Mrinal R.; Tripathi, A.K.
Abstract: NiFe based layered hydroxides (LDH) is an efficient oxygen evolution catalysts used in energy conversion and storage devices. Herein, we used in-situ electrochemical impedance spectroscopy (EIS) to study the role of Fe in improving the oxygen evolution reaction (OER) of NiFe-LDH, as an alternative to expensive techniques. Optimized Ni0·46 Fe0.54 -LDH showed Tafel slope of 49 mV dec −1 and over potential of 340 mV at 10 mA cm −2 . Increase in Fe content in NiFe-LDH, lowered the average oxidation of the Ni, revealing the stabilization of lower oxidation state of Ni. Potential dependent EIS supported this effect showing that multi-metal LDH favors the surface intermediate stabilization thereby reducing the overall charge transfer resistance at interface compared to mono metal catalysis. Surface intermediate relaxation process is dependent on Fe content and is playing a role in deciding the rate limiting step. The Fe– O –Ni linkages in FeOx -NiFe-LDH systems exert partial charge transfer activation for OER process. A prototype demonstration of overall water splitting using a photovoltaic-electrolyser assembly is conducted with Ni0·46 Fe0.54 -LDH as bifunctional catalysts which yields a constant current density of 10 mA cm −2 at a Voc = 1.65 V. Present study provide experimental evidence of improved activity of FeOx -NiFe-LDH with the help of potential dependent EIS studies and makes practically attractive for renewable energy conversion and storage applications. Graphical abstract: Image 1 Highlights: Role of Fe content in NiFe-LDH in tuning the water oxidation is investigated. Decrease in Ni average oxidation showed stabilization of lower Ni oxidation state. Surface intermediate relaxation process is rate limiting step in OER reaction. Fe-O-Ni linkages in FeOx-NiFe-LDH exert a partial charge transfer activation effect. Prototype demonstration of a photovoltaic-electrolyser assembly was done.